STUDIES ON ARSENICAL CREOSOTE AS A WOOD PRESERVATIVE FOR MARINE STRUCTURE- PART II-OBSERVATION ON LEACHING CORROSIN AND RESISTANCE TO BORER ATTACK - NAIR, N, "UNNIKRISHNAN; PILLAI, A. G. GOPALAKRISHNA; BALASUBRAMANYAN, R (Fishery Technology, 2016)
A detailed study on arsenical creosote with reference toleaching, corrosion and anti-borer p-roperties was carried out,Results showed that aging had vety little effect on the preservativewhich suggested better fixation of the preservative into the wood.Corrosion of mild steel, galvanised iron, aluminium-magnesiumalloy (M57S) and copper panels in the preservative was found tobe negligible, Normal creosote and low temperatme creosote ofRegional Research Laboratory, Hyderctbad, both fortified witharsenic trio:xjde resisted borer damage on wooden pands for aperiod of over five months in the port of Cochin. The perfor-manceof low temperature creos.ote fortified with arsenic was foundto be equally satisfactory when compared to normal creosote for-tifiedin the same manneL A loading of 208.6 Kgsjml> for Haldtt(Adina cordifolia) and 138 Kgsjm'Â§ for Mango (lvfangifera indica)in the case of normal creosote and 177 Kgs/m :e. for Mango thecase of RRL creosote were found to be su.fficient for treatingthe wood.